The Using of Students’ Modules and Role on Learning Achievement in Covid-19 Pandemic - Rudi - Hermawan; Sudji Munadi; Mazda Leva Okta Safitri (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
The article explored the relationship between the use of teaching materials and the role of students with learning achievement during the COVID-19 period. The research was correlational quantitative approach with research subjects at the Mechanical Engineering Vocational School. Collecting data using interviews, documentation, and questionnaires. Pearson Product Moment correlation technique analysis, t-test, and F test, with SPSS software. The results showed that the use of teaching materials is an external factor that supports the effectiveness of student learning outcomes, adds motivation to the spirit of learning, improves skills directly, creates an independent learning atmosphere according to interests, speed and a certain way, was able to independently assess and evaluate the results of using materials. The role of students when learning from home (BDR) was not good enough, caused by various factors, namely the role of educators which must be maximized again, providing motivation and support even though learning was carried out online from home. The role of students, in this case, was actively paying attention to the presentation of learning with modules through the zoom platform, understanding learning materials, summarizing and concluding subject matter, participating actively in asking questions, and responding either individually or in groups. Learning achievement produced by students in the Covid-19 era could not be separated from the effectiveness of using modules, but there were still obstacles experienced by students when learning from home online, less active participation during the learning process, and late in collecting assignments. Keywords: Teaching Materials, Learning Achievement, Learning Pandemic Era